Training Students with Data Mining and GIS - Taha Yaseen, Ali; S. Tywofik, Zaki; Q. Mohammed, Mohammed (International Journal of Engineering and Technology, 2018)
Present in colleges to day the students have course of the data mining which is the procedure of mining knowledge from data to solve problems, gain knowledge and set expectations. Students in the course have acquired a great knowledge and understanding of the processes involved in extracting data through the experience gained in data extraction applications. The course has shown that students' education is appropriate and can be successful. In this research students apply their expertise on data taken from the Iraqi Health Ministry to persons infected with hepatitis in Iraq's cities to discover knowledge about the virus, and that the use of geographic information system (GIS) to display the result to extract the data in the map of Iraq, which give force for them work and that new way to combine data mining with GIS.Â Â